2020
DOI: 10.1093/gbe/evaa240
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Transcriptome Analyses of Native Symbionts Reveal Host Coral Genomic Novelties for Establishing Coral–Algae Symbioses

Abstract: Reef-building corals and photosynthetic, endosymbiotic algae of the family Symbiodiniaceae establish mutualistic relationships that are fundamental to coral biology, enabling coral reefs to support a vast diversity of marine species. Although numerous types of Symbiodiniaceae occur in coral reef environments, Acropora corals select specific types in early life stages. In order to study molecular mechanisms of coral-algal symbioses occurring in nature, we performed whole-genome transcriptomic analyses of Acropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 106 publications
2
51
0
Order By: Relevance
“…The IVB5 line also provides a system to explore molecular mechanisms involved in coral-dinoflagellate symbiosis. Studies should strive to duplicate results of previous transcriptomic studies (Yuyama et al, 2018;Yoshioka et al, 2021) and of single-cell RNA-seq analyses (Hu et al, 2020). If genes that play pivotal roles in the symbiosis are found in future studies, an introduction of CRISPR/Cas9-mediated genome editing method seems challenging (Cleves et al, 2018).…”
Section: Future Studies Using This In Vitro Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVB5 line also provides a system to explore molecular mechanisms involved in coral-dinoflagellate symbiosis. Studies should strive to duplicate results of previous transcriptomic studies (Yuyama et al, 2018;Yoshioka et al, 2021) and of single-cell RNA-seq analyses (Hu et al, 2020). If genes that play pivotal roles in the symbiosis are found in future studies, an introduction of CRISPR/Cas9-mediated genome editing method seems challenging (Cleves et al, 2018).…”
Section: Future Studies Using This In Vitro Systemmentioning
confidence: 99%
“…Modulation of coral host inert immunity allows symbiosis of given species of algae in their cytoplasm (Davy et al, 2012). Although many studies has attempted to explore cellular and molecular mechanisms of coral-dinoflagellate endosymbiosis (Dove, 2004;Davy et al, 2012;Yuyama et al, 2018;Weis, 2019;Rosset et al, 2021;Yoshioka et al, 2021), many questions remain, especially regarding recognition mechanisms involved in the initial contact of animal and algal cells, cellular mechanisms allowing dinoflagellate endocytosis and maintenance of endosymbiosis, especially at the single-cell level (Davy et al, 2012). Recently, our knowledge of mechanisms involved in cnidaria-dinoflagellate symbiosis has been advanced by studies using the sea anemone, Exaiptasia diaphana (Weis, 2019), and the soft coral, Xenia sp.…”
Section: Introductionmentioning
confidence: 99%
“…In Smic-inoculated larvae, a limited number of DEGs was shared between time points (3 to 24 hpi) (Figure 2A), suggesting that gene expression changes of host corals were drastic during initial contact with native symbionts. Next, we compared the DEG repertoires at 24 hpi with a previous study analyzing transcriptomic responses of A. tenuis larvae during symbiosis establishment (4, 8, and 12 days postinoculation (dpi)) 30 . Six DEGs were observed at all time points, 24 hpi, and 4, 8, and 12 dpi (Supplementary Figure 2), and only 2 upregulated DEGs and 38 downregulated DEGs identi ed at 24 hpi in this study were also observed at 4 dpi (Supplementary Figure 2), indicating that DEG repertoires between initial contact and symbiosis establishment are independent, but that the limited array of genes that is constantly differentially expressed in both stages could be important for transition of symbiosis phases.…”
Section: Comparison Of Deg Repertoires Between Initial Contact and Symbiosis Establishmentmentioning
confidence: 99%
“…tenuis to its native symbiont, S. microadriaticum (Smic) 30 . To study molecular responses that occur in coral larvae during initial contact with native symbionts, we analyzed the transcriptome of A. tenuis larvae at 1, 3, 6, 12, and 24 h post-inoculation (hpi) with symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these recent advances, many aspects of the changes dinoflagellate undergo during coral endosymbiosis establishment remain unclear. Previous studies have established a model endosymbiosis system consisting of monoclonal alga and juvenile corals, and transcriptome data for these coral–alga complexes have been published, with a focus on coral gene expression [ 11 , 14 , 15 , 16 ]. By contrast, the gene expression levels of dinoflagellate during coral endosymbiosis have not been investigated due to a lack of transcriptome data for the non-symbiotic state.…”
Section: Introductionmentioning
confidence: 99%